DIGITAL INFORMATION’S INFLUENCE ON FORMING TOURISM EVENT IMPRESSIONS: THE INTERPLAY OF GENDER AND TOURISM TYPES - Amany E. SALEM; Thowayeb H. HASSAN; Mahmoud I. SALEH; Mostafa A. HASSANIN; Hassan Marzok Elsayed MAHMOUD; Ashraf Mohamed ANAS; Hadeel Sa'ad AL-HYARI; Hisham Mohammad AL-SMADI; Yasmine E. HAMZA (Geo Journal of Tourism and Geosites)
Digital information plays a crucial role in shaping tourists' expectations and impressions of potential destinations and activities. This study explores how perceptions of digital information vary across different tourism experience types (adventure, leisure, cultural) and examines the complex interactions between digital information perception and tourism engagement. A survey was conducted among tourists actively participating in various tourism types to collect data on their digital information consumption habits and their influence on their overall perceptions. The findings reveal that leisure and adventure tourists demonstrate a stronger initial reliance on digital information compared to cultural tourists. However, all tourism types exhibit negative interaction effects, suggesting diminishing returns of digital information as engagement increases. Specifically, leisure and adventure tourism show stronger positive main effects on digital information perception compared to cultural tourism. Interestingly, leisure and adventure tourism also display more pronounced negative interaction effects than cultural tourism. These insights suggest that destination marketers should employ nuanced, personalized strategies catered to specific tourism types, considering the varying levels of digital information reliance and the changing needs of tourists as their engagement progresses. For leisure and adventure tourism, this may involve front-loading comprehensive digital information, while cultural tourism may benefit from a more consistent information flow throughout the experience. These tailored approaches could enhance destination brand affinity and improve the overall tourist experience across different tourism segments.